Mesoporous carbons from self‐assembled polymers. Issue 14 (11th April 2022) - Robertson, Mark; Zagho, Moustafa M.; Nazarenko, Sergei; Qiang, Zhe
Abstract: Polymer self‐assembly provides a robust and cost‐efficient nanomanufacturing platform for enabling a broad range of applications, such as microelectronics, drug delivery, and separation membranes. This review focuses on discussing the progress and opportunities of self‐assembled polymer in the synthesis of mesoporous carbons (MCs), which have aroused significant research interests over the past decades. Specifically, we will discuss the two most established approaches for converting nanostructured polymers to MCs, including templating‐based and direct pyrolysis‐based methods. We will also review the fundamental ordering mechanisms and kinetics of these polymeric systems and discuss the recent development of engineering methods for providing on‐demand control over the pore size and morphology of MCs. Additionally, this review article also includes a section focusing on the strategies to further functionalize these materials from self‐assembled polymers to enhance their performance, such as chemical activation, heteroatom doping, introduction of nanoparticles into the carbon matrix, and enhancing graphitization degree of carbon walls. Finally, a brief perspective is provided about the emerging research opportunity in this exciting field. Abstract :